Marcel Bataillon: LA COLONIA, ENSAYOS PERUANISTAS. Compilación de Alberto Tauro. Edición Universidad N.M. de San Marcos, Lima, 1955, XV + 203 pp. - Maticorena Estrada, Miguel (Revista Histórica, 2025)
Sin resumen.